Does early educational tracking contribute to gender gaps in test achievement? A cross-country assessment - Theresa Lorenz; Alyssa Schneebaum (Journal of Economics and Statistics, 2024)
On average, boys score higher on math achievement tests and girls score higher in reading; these gaps increase between primary and secondary school. Using PISA, PIRLS, and TIMSS data, we investigate the role of early educational tracking (sorting students into different types of secondary schools at an early age) on gender gaps in test achievement in a cross-country difference-in-differences framework. We find strong evidence that early tracking increases gender differences in reading. For math test scores, we do not find consistent evidence that early tracking contributes to the gender gap.
Keywords: I24; I28; J16; H52; 330; early tracking; educational systems; gender gaps; PIRLS; PISA; TIMSS